Business plan for “Mammadov and Company” LLC - Mammadov, Emin (ADA University, 2019)
Nowadays, almost every day we can hear about a new coffee opened near our workplace, see the commercial of a new company offering interesting service or one of our friends tells us about a new business idea which can be interesting for the audience. We regularly see how new start-ups come to the stage. But also we hear about a lot of unsuccessful or closed start-ups. About three-quarters of venture-backed firms in the U.S. don't return investors' capital, according to recent research by Shikhar Ghosh, a senior lecturer at Harvard Business School (as cited by Gage, 2012). Many founders can’t do what is needed for a business to take off (Arnaud, 2018). Research shows that one of the main reasons why start-ups fail is the lack of skills and experience in their founders and team members. Even if the author of the idea, the founder of one particular start-up has needed skills, it’s always hard to find the right team to manage the business. With an inexperienced team, such steps as correctly allocating spendings, doing correct marketing, calculating retail prices, presenting product or service you offer as it’s needed to be presented, approaching customers, and even writing a post in social network page can be challenging. If to take into consideration the more difficult actions needed to be taken, the chance of the start-up to become a successful one is almost impossible. “Mammadov and Company” LLC (or called “M&C”) is a business consulting company founded to provide services mostly for the start-ups. The idea of this company is to provide high-quality services by experienced young people for much lower prices than competitors. The company provides its customers with all of the services they need starting from the very beginning of their start-up.
Keywords: Business; Business plan; Business consulting company; Limited Liability Company